Pengaruh Model Pembelajaran Snowball Throwing Terhadap Kemampuan Menulis Teks Cerpen Pada Siswa Kelas IX SMP Negeri 4 Medan Tahun Ajaran 2022/2023 - Suri Andary; Syamsul Arif (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
The aim of this research is to explain the influence of the Snowball Throwing Learning Model on the Ability to Write Short Story Texts in Class IX Students of SMP Negeri 4 Medan in the 2022/2023 Academic Year. The population of this study was all students in class IX of SMP Negeri 04 Medan consisting of 11 classes with a total of 324 students. The samples taken were class IX-1 as the experimental class and class IX-2 as the control class. The method used in this research is an experimental method with a two group post-test design, with a research instrument in the form of an assignment to create a short story text. The experimental class got an average score of 78.33 while the control class got an average score of 73.50. This means that the value obtained by the experimental class is higher than the value obtained by the control class. Based on the results of the analysis, it was found that the data results were normally distributed. After carrying out a normality test of p > 0.05 at a significant level, the results of the normality test of the experimental posttest data were (0.059 > 0.05), and the normality test results of the control posttest data were (0.200 > 0.05). The results of the homogeneity test for the ability to write short story texts were p-value > α = 0.05 with posttest results for the experimental class and control class of 0.070 > α = 0.05 and the hypothesis test obtained a significance value of 0.045.